A163 THE ROLE OF ANTIBIOTICS IN ACUTE UNCOMPLICATED DIVERTICULITIS: A SYSTEMATIC REVIEW AND META-ANALYSIS. (1st March 2018) - Mocanu, V; Dang, J; Switzer, N; Tavakoli, I; Tian, C; de Gara, C; Birch, D W; Karmali, S
Abstract: Background: Diverticular disease is the most common disease of the large bowel and poses a significant burden on healthcare resources. In the United States alone, the cost of diverticular disease has been estimated to be over $3 billion making it the fifth most important gastrointestinal disease economically. The use of antibiotics in the management of acute uncomplicated diverticulitis (AUD), however, is primarily based on expert opinion as current high-quality evidence is lacking. Recent studies have not only questioned the optimal type and duration of antibiotic regimens, but whether antibiotics provide any benefit in the treatment of AUD. Aims: The aim of the present study was to perform a systematic review of the literature to determine the role of antibiotics in the management of AUD. Methods: A comprehensive literature search for both published and unpublished studies of "diverticulitis AND antibiotics" from 1946 to June 2017 was performed using Medline, EMBASE, Scopus, the Cochrane Library, and Web of Science databases. Included studies were assessed for methodological quality and bias. Abstracts and titles were screened for inclusion by two independent reviewers as per PRISMA guidelines. Outcomes assessed in the meta-analysis included treatment failure, recurrence, abscess, perforation, bleeding, stenosis, hospital length of stay, need for elective surgery or emergent surgery and overall morbidity using the Revman 5.3 software. Results: Eight studies with 2469 patients were included for review. Overall complication rates (Figure 1) were not statistically significant between groups (OR 0.72; CI 0.45 to 1.16; P = 0.18), but antibiotic use was associated with a longer length of stay in hospital (MD -1.13; CI -1.77-to -0.48; P = 0.0006). Subgroup analysis revealed no difference in readmission rates (OR 0.77; CI 0.55 to 1.09; P = 0.14), treatment failure rates (OR 0.43; CI 0.15 to 1.27; P = 0.13), progression to complicated diverticulitis, or increased need for elective (OR 0.66; CI 0.24 to 1.79; P = 0.80) or emergent surgery (OR 0.69; CI 0.24 to 1.79; P = 0.80) between study groups. Conclusions: Antibiotic use in patients with acute uncomplicated diverticulitis is not associated with a reduction in major complications, readmissions, treatment failure, progression to complicated diverticulitis, or need for elective and emergent surgery. However, it increases the length of hospital stay. Antibiotics may not be warranted, but given the risk of selection bias in included studies, further randomized trials are needed to clarify the need for antibiotics in uncomplicated diverticulitis. Funding Agencies: None